Situated harmful traditional practices in South-western Nigeria: recent Progress, challenges and lessons for policy engagements (2023)
Harmful traditional practices (HTPs) are discretionary social challenges facing mostly girls and women of all ages and sizes. Wherever it occurs, HTPS rob girls and women of their childhood, deny them the chance to determine their own future as well as threaten the well-being of individuals, families and societies. Previous study have worked on various interventions such interagency statement on eliminating female genital mutilation, global strategy efforts and lots more. None of these studies have been able to analyse harmful traditional practices in south Nigeria vis-a-vis recent progress in its reduction, pending challenges and lessons for policy engagements, hence this study did a re-assessment of the state of things in terms of its reduction efforts, pending challenges, lessons, effects and plausible solutions to htps for policy engagements. The study adopted a mixed methods research design of the explanatory type (qua! + QUAN). The study deployed a two-prong approach in which focus group discussion sessions were conducted and thematically analysed to design the quantitative instrument. The population of the study comprised all elders who are 50 years and above. The multi-stage sampling procedure was adopted. The first stage was the total enumeration of states in southwest Nigeria. The random sampling technique was used to select 18 Local government areas (One per Senatorial District) in SW, Nigeria. From each of the LGAs, 35 participants who are 50 years and above were purposively selected. A self-designed instrument titled Questionnaire on Harmful Traditional Practices (QHTPs, r=0.82) with sub-scales was used. It was also translated in local dialect for easy understanding and responses. The study which began in 2019 and due to covid_ 19 pandemic lasted two and half years. Recent progress have been made, some challenges have been discovered which are epistemic understanding; lack of focus on prevention and imperatives for ministers to pursue short-term solutions; lack of continuity of programmes meant to dismantle htps. and few lessons have been learnt It is recommended that through education, collaborative engagements and seminars, the reduction efforts of harmful traditional practices in southwestern Nigeria can be achieved holistically.